Tourism Entrepreneurship in Portugal and Spain Competitive Landscapes and Innovative Business Models - Leitão, João; Ratten, Vanessa; Braga, Vitor (Tourism, Hospitality & Event Management, 2022)
XI, 282 p. 26 illus.